Computational Stylometric Approach to the Dead Sea Scrolls: Towards a New Research Agenda - Hecke, Pierre Jacques Paul van (Dead Sea discoveries, 2018)
The question of how to classify the different texts of the Dead Sea Scrolls is a central issue in scholarship. There is little agreement or even little reflection, however, on the methodology with which these classifications should be made.